Screening Instruments for Depression in Advanced Cancer Patients: What Do We Actually Measure?. Issue 6 (16th November 2012) - Warmenhoven, Franca; van, Chris; Vissers, Kris; Prins, Judith
Abstract Background Patients in a palliative care trajectory frequently suffer from depression. To distinguish depression from normal sadness, the use of screening instruments could facilitate the diagnostic process. However, in palliative care, screening instruments may not discern physical symptom burden from psychological distress, due to the high number of physical symptoms in palliative patients. Objectives The aim of this study was to explore physical symptom burden and psychological distress in patients with advanced cancer in relation to scores on screening instruments for depression. Methods Patients with advanced cancer were asked to fill out the Beck Depression Inventory (BDI‐II), Beck Depression Inventory Primary Care (BDI‐PC), Hospital Anxiety and Depression Scale (HADS), and Memorial Symptom Assessment Scale Short Form (MSAS‐SF). The relationship between scores on screening tools for depression and different physical symptom clusters was explored. Results In the sample of 65 patients, screening instruments for depression correlated highly with different somatic symptom clusters. The BDI‐II cognitive subscale was the only scale that was not significantly correlated with any of the somatic symptom clusters. Conclusion Screening tools for the detection of depression in patients with advanced cancer may not provide an accurate evaluation of depression. These tools seem to measure physical symptom burden as well, especially when patients suffer from symptoms of the clusters fatigue/anorexia/cachexia, neuropsychology, debility, or pain. In this study, the BDI‐II cognitive subscale seems to differentiate best from somatic symptom burden.